Parents' Contribution in Instilling Islamic Dress Ethics in Teenagers - Fitri rahmayanti; Wilrahmi Izzati (Al-Kahfi: Jurnal Pendidikan Agama Islam, 2024)
Ethical dress codes are crucial for today's youth. Parents play a crucial role in guiding their children on how to dress appropriately. This study aims to analyze adolescents who dress inappropriately according to Islamic law. Many teenagers today wear the hijab but don't cover their chests, while others wear the hijab but wear short-sleeved clothing that exposes their curves. This study employed a qualitative method with a case study design. Data were collected from several parents with adolescent children in Jorong Padang Canduh, Kinali District, West Pasaman Regency. The techniques used in this research are observation, interviews, and documentation. The results of the analysis show that it is known that the role of parents in fostering Islamic dress ethics for teenagers in Jorong Padang Canduh, Kinali District, West Pasaman Regency is by directing, parents direct to cover the genitals according to Islamic teachings and giving gentle advice without putting pressure on teenagers in dressing Islamically, then by providing motivation such as parental encouragement to teenagers by providing knowledge about good Islamic dress, fulfilling the needs of teenagers by buying clothes according to Islamic law, then also by providing supervision such as giving warnings to teenage girls if they do not dress according to Islamic law, and providing regulations in dressing according to Islamic law.